The Rise of AI-Assisted Consumer Information Search: An Exploratory Study on Shifting Purchase Decision Behavior in Indonesia - Dedy Budiman (Fundamental and Applied Management Journal, 2026)
This study investigates the shifting patterns of consumer information-seeking behavior in Indonesia amid the rapid adoption of artificial intelligence (AI) search tools such as ChatGPT, Google AI Mode, Gemini, and Perplexity. Grounded in the Technology Acceptance Model and Consumer Decision Journey framework, the study proposes an integrated conceptual model in which AI adoption drives information processing, builds consumer confidence, and shapes brand consideration through AI-mediated recommendations. An exploratory quantitative survey was conducted via Google Forms from March 3 to 13, 2026, distributed through professional networks including Sales Director Indonesia (SDI), the Indonesian Marketing Teachers Association (AGMARI), and corporate client networks spanning multiple provinces. A total of 1,617 responses were collected (1,596 valid). The findings reveal that 74.6% of Indonesian consumers have used AI tools for product research, 26.4% are heavy users, 52.3% are influenced by AI brand mentions, and 79.8% perceive AI as accelerating their decision-making. Notably, consumers aged 55 and above demonstrated the highest AI-first adoption rate (24.2%), challenging conventional assumptions about generational technology adoption — a phenomenon herein termed the Silver Surfer Paradox. The study contributes theoretically by extending the Consumer Decision Journey framework to AI-mediated information environments and empirically by repositioning task complexity over digital nativity as a stronger predictor of AI adoption. Practically, the findings establish Generative Engine Optimization (GEO) as a strategic imperative for digital business in the AI era.